Inovasi dan Digitalisasi Pemasaran Budidaya Ayam Caru Sebagai Sarana Upakara Hindu di Desa Banjar Anyar Kecamatan Kediri Kabupaten Tabanan - Nyoman Purnama; Nengah Widya Utami; I Made Dwi Hita Darmawan (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2023)
Bali is one of the islands in Indonesia with diverse culture and traditions. Where one of the cultures and traditions is passed from generation to generation is in the form of religious ritual activities. This activity is an indispensable part of people's daily lives. Every ceremony held by Hindus in Bali is always accompanied by offerings, like the mecaru ceremony. In the caru worshiping ceremony, animals or animals are always used to worship, including free-range chickens with typical feather colors such as white, red, yellow, black and brumbun (many colors). Rituals in Bali often take place on certain days, seasons, or times, so at certain times, the demand for ritual vehicles, including chickens, is very high and it is difficult to find special colors. show that. Ajik Chicken Farm and Premium Free-Free Chicken Farmers Community are small and medium-sized enterprises in the field of free-range Chicken Farming. Different types of free-range chicken breeds are produced at the business located in Banjar Anyar village, Kediri Tabanan district, Bali. These include Mentari chickens, chickens, male chickens, Joper chickens and Afkir chickens. The implementation of Community Services for Beginners with the theme “Innovation and digitalization of commercialization of Caru Chicken Farming as a means of Hindu rituals in Banjar Anyar village, Kediri district, Tabanan district” is divided into multiple stages, namely: problem identification, implementation of activities, program support, and monitoring and evaluation. Overall, the implementation of this PMP activity went well, partners felt supported and enthusiastically participated. This PMP activity will support partners in their marketing and promotional activities so they can improve their knowledge and skills in information systems and social media management as well as financial management. In addition, this activity also provides training on Caru chicken marketing using web applications, electronic media publications, videos of implementation of activities and publications in recognized journals.